Another world is possible : Globalization and Anti -Capitalism (UK Merlin, 2006)
Documentary on the activism of the United Nations Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) regarding the discrimination against women in five countries of South Asia, specifically women in Bangladesh, India, Nepal, Pakistan and Sri Lanka, and whose governments have pledged to take action to reduce the disparities in wealth and provide access to resources for women.
Keywords: Nonfiction films